The Comprehensive Systematic Review of Association of Posterior Capsular Opacification (PCO) to IOL Material and Design - Agnes Poppy Melina; Putu Ayu Wedayanti Daniputri; Ni Putu Ayu Rahmayanti (The Indonesian Journal of General Medicine, 2026)
Introduction: Posterior capsule opacification (PCO) remains the most common long-term complication of modern cataract surgery, leading to visual degradation and necessitating Nd:YAG laser capsulotomy. The risk of PCO is influenced by intraocular lens (IOL) characteristics, including material, optic edge design, and haptic configuration. However, the relative importance of these factors and potential interactions remain a subject of extensive research with sometimes conflicting findings. Methods: This comprehensive review synthesizes evidence from 80 studies, including randomized controlled trials, cohort studies, systematic reviews, and meta-analyses, that investigate the association between IOL characteristics and PCO development. Studies were screened based on predefined criteria including adult patients, uncomplicated cataract surgery, comparison of IOL materials/designs, quantitative PCO assessment, and a minimum follow-up of 6 months. Data were extracted on IOL specifications, PCO assessment methods, outcomes (scores, Nd:YAG rates), and study methodology. Results: The evidence robustly identifies a sharp posterior optic edge as the most critical design feature for PCO prevention, demonstrating significant benefits across all IOL materials (PMMA, silicone, acrylic) with up to a 35% absolute reduction in 9-year Nd:YAG rates (Haripriya et al., 2017). Regarding material, hydrophobic acrylic IOLs are consistently superior to hydrophilic acrylic, with meta-analyses showing a standardized mean difference of -1.80 in PCO severity and a relative risk of 6.96 for Nd:YAG capsulotomy favoring hydrophobic materials (Li et al., 2013; Wu et al., 2022). PMMA IOLs are associated with significantly higher PCO rates compared to modern foldable materials (Kobayashi et al., 2000; Sundelin et al., 2001). Comparisons between silicone and hydrophobic acrylic IOLs show time-dependent outcomes: acrylic may have an early advantage, but silicone may demonstrate better long-term (≥6 years) performance (Kwon et al., 2022). Haptic design (1-piece vs. 3-piece) shows no significant long-term impact on PCO when material and edge design are controlled (Leydolt et al., 2007; Haripriya et al., 2025). Surface modifications like heparin coating do not confer additional PCO protection (Krall et al., 2015). Discussion: The synthesis clarifies apparent conflicts in the literature by highlighting confounding variables, particularly the interaction between material and edge design, and the critical role of follow-up duration. The "barrier effect" of a sharp edge is the predominant mechanistic factor inhibiting lens epithelial cell migration. Significant performance variations exist even within the same material category, emphasizing that specific IOL platform characteristics are as important as broad material classification. Conclusion: For optimal PCO prevention, IOL selection should prioritize a sharp posterior optic edge design. Among acrylic materials, hydrophobic variants are preferred over hydrophilic. For patients with long life expectancy, silicone IOLs with a sharp edge may offer a long-term advantage, though this requires further validation. Haptic design is a secondary consideration. In resource-limited settings, adopting sharp-edged PMMA IOLs can substantially reduce the Nd:YAG capsulotomy burden.